Liver Transplantation for Hepatocellular Carcinoma With Bile Duct Tumor-Associated Thrombi: A Systematic Review and Pooled Analysis - Kim, Steven C.; Bolognese, Alexandra C.; Little, Christopher J.; Hitchcock, Mary E.; Leverson, Glen E.; Al-Adra, David P. (Frontiers in Transplantation, 2022)
Introduction: The significance of bile duct tumor-associated thrombi in patients undergoing transplantation for hepatocellular carcinoma (HCC) is controversial. Therefore, we performed a systematic review of the literature with pooled analysis to investigate the impact of biliary invasion on HCC recurrence and patient survival. Methods: Of 1 584 references screened, eight were included for analysis. Demographics, patient and tumor factors, recurrence, and survival data were analyzed. Time to recurrence and death were extracted from each paper by cross-referencing survival curves. Results: A total of 35 patients across eight studies were pooled for analysis when follow-up data were available. At one year, 92.9% of patients undergoing transplantation for HCC with bile duct thrombi were alive. Overall survival at three and five years was 65.5% and 49.6%, respectively. At one year, 21.6% of patients had recurrence of their disease, while at three years, 50.4% of patients had recurrence. Of those patients with recurrence in the first year, 71.4% recurred within the first three months after transplantation. Conclusions: Overall patient survival decreased within the first five years, but then stabilized. The 5-year survival rate of 49.6% in this pooled analysis is lower than that reported for patients undergoing transplantation for HCC within the Milan criteria (50-78%) or recent reports in patients with portal vein involvement (63.6%), though data is limited by a lack of long-term follow-up in this understudied population. Transplantation for patients with HCC with bile duct involvement may be a viable treatment option, warranting further investigation.